Butterfly - Smile; Uhlmann, Robert; Rex, Robin; EMI Music (Denmark : EMI Music, 1998)
Contains three versions of the single.
CD 1 : Butterfly / (2:55) -- Butterfly (Pan Ace Radio Mix) / (2:59) -- Butterfly (Anaconda Remix) / (4:25).
Koleksi Khas Wiramanja.
Title from disc label.